2016
DOI: 10.1111/gcb.13467
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of water table lowering and nitrogen deposition in affecting greenhouse gas emissions from a Tibetan alpine wetland

Abstract: Rapid climate change and intensified human activities have resulted in water table lowering (WTL) and enhanced nitrogen (N) deposition in Tibetan alpine wetlands. These changes may alter the magnitude and direction of greenhouse gas (GHG) emissions, affecting the climate impact of these fragile ecosystems. We conducted a mesocosm experiment combined with a metagenomics approach (GeoChip 5.0) to elucidate the effects of WTL (-20 cm relative to control) and N deposition (30 kg N ha yr ) on carbon dioxide (CO ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 70 publications
(92 reference statements)
3
46
1
1
Order By: Relevance
“…Water table depth is one of the key regulators controlling GHG emissions and soil subsidence in peatlands (Couwenberg et al, ; Malone et al, ; Wang et al, ; Yang et al, ). Rewetting of drained peatlands has the highest priority for addressing soil subsidence and mitigating CO 2 emissions from peat oxidation (FAO & Wetland International, ; Knox et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Water table depth is one of the key regulators controlling GHG emissions and soil subsidence in peatlands (Couwenberg et al, ; Malone et al, ; Wang et al, ; Yang et al, ). Rewetting of drained peatlands has the highest priority for addressing soil subsidence and mitigating CO 2 emissions from peat oxidation (FAO & Wetland International, ; Knox et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The experiment consists of duplicated control (with submerged soils) and WTD (−20 cm relative to control) treatments in an alpine wetland dominated by Carex pamirensis (cf. Wang et al 3536. for details of the experimental design).…”
mentioning
confidence: 99%
“…In this study we comprehensively revealed the mechanisms underlying the diurnal and seasonal dynamics of net CH 4 uptake at the ecosystem scale in an alpine meadow, which is of critical importance for methane budget estimation of Qinghai‐Tibetan Plateau. Most previous studies only measured CH 4 flux a few times in a day or during a season, and these measurements were used to represent the average daily or seasonal CH 4 fluxes (Liu et al, ; Voigt et al, ; Wang et al, ; Zhao et al, ). However, using average values of a period in a day or a season to represent daily or annual methane fluxes may lead to large misestimation of CH 4 budget in ecosystems with highly variable diurnal and seasonal methane flux.…”
Section: Discussionmentioning
confidence: 99%